Pengembangan Promosi Kesehatan Gigi dan Mulut Pada Masyarakat Pesisir - Jalil, Muh. Alfi Syahrin; Faizal, Prayoga Ridha; Ramdhani, Astri; Setiawan, Muh Asman; Afdilla, Nia; Sofyan, Suhikmah; Nuraisyah; Razak, Adriatman (ADPERTISI, 2025)
Oral health promotion is a preventive effort aimed at increasing awareness and healthy behaviors from an early age. This study was conducted in Bajo Soropia Indah Village to evaluate the effectiveness of oral health promotion in improving children's knowledge and tooth brushing habits. The methods used included health education, demonstration of proper tooth brushing techniques, topical fluoride application, and plaque index examination as an indicator of oral hygiene. The results showed that all child participants (n=6) had poor plaque index scores (100%). Following the implementation of the health promotion program, an increase in knowledge and a shift in behavior regarding oral hygiene are expected. The findings emphasize the importance of educational interventions and routine check-ups in preventing dental and oral diseases among children in remote areas. Community-based health promotion programs have proven to be a relevant approach in improving children's oral health status.